Kecerdasan Buatan dan Hak Asasi Manusia: Analisis Etika dan Kerangka Hukum di Era Digital - Salman Al Farisi, Salman Al Farisi; Sri Puji Ningsih; Arda Fairuzaki, Arda Fairuzaki; Novita Mayasari, Novita Mayasari; Salman Nurfarizi, Salman Nurfarizi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The rapid advancement of artificial intelligence (AI) in the digital age offers substantial benefits by enhancing efficiency and productivity. Nevertheless, these developments also pose significant challenges to the protection of human rights. Issues such as privacy violations, algorithmic bias, discrimination, and opaque automated decision-making highlight the need for a strong integration of ethical values and legal frameworks in the use of AI. This study applies a normative legal method supported by literature-based research to examine the existing regulatory frameworks and the ethical principles underpinning them. The findings indicate that ethical principles such as transparency, accountability, fairness, and human-centeredness serve as essential moral guidelines to prevent AI misuse. Meanwhile, legal rules ensure certainty, establish accountability mechanisms, and provide sanctions for violations. The synergy between ethics and law forms a crucial foundation to ensure that technological innovation aligns with the protection of human rights, upholds human dignity, and supports the creation of a safe and just digital environment